1985
DOI: 10.3109/00365518509155265
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide determination in the choice of treatment in diabetes mellitus

Abstract: The predictive value of the intravenous glucagon test in assessing the requirement of insulin therapy in diabetes mellitus was evaluated in 105 adult diabetics. Basal and stimulated C-peptide concentrations and increments of C-peptide concentration were examined separately among newly and previously diagnosed diabetics. The poststimulatory C-peptide concentration of 0.6 nmol/l (Novo, antibody M 1230) proved to be the most reliable basis for the choice of therapy. Adequate therapy could have been assessed in 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Although previous studies have investigated the association between markers of beta-cell function and future insulin use, to the best of our knowledge, none has comprehensively examined the relationships of various clinical variables, including body mass index, fasting plasma glucose levels, and serum and urinary c-peptide levels with future insulin use [4,5,7,8,11,[14][15][16]. As expected, we found that increased FPG was associated with future insulin use.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although previous studies have investigated the association between markers of beta-cell function and future insulin use, to the best of our knowledge, none has comprehensively examined the relationships of various clinical variables, including body mass index, fasting plasma glucose levels, and serum and urinary c-peptide levels with future insulin use [4,5,7,8,11,[14][15][16]. As expected, we found that increased FPG was associated with future insulin use.…”
Section: Discussionsupporting
confidence: 70%
“…sulin resistance play critical roles in the development of hyperglycemia in patients of type 2 diabetes, measurement of the serum c-peptide levels (scPr) and urinary c-peptide levels (ucPr), which are known to be useful markers of beta-cell function, may also provide important information for the choice of therapy [3][4][5][6][7][8][9][10][11][12][13]. However, few studies have been conducted to identify factors that might determine or predict the therapy of choice in type 2 diabetic patients.…”
mentioning
confidence: 99%
“…The scatter of the values in each group was, however, wide. This finding is in accord with observations from previous studies where C-peptide concentrations in younger type 2 diabetic patients have been determined [7,12,18,23], Very low values were found only in diabetics treated with insulin, and it is obvious that patients with a disease resembling type 1 diabetes are in cluded in this group. On the other hand, exog enous insulin may suppress endogenous insu lin production and thus lead to low C-peptide concentrations [5], Our observations about the lowered diurnal C-peptide profile during insulin therapy in 1 elderly diabetic patient gives further support to this view.…”
Section: Discussionsupporting
confidence: 82%
“…Most elderly diabetics have the type 2 disease (noninsulin-dependent dia betes mellitus, NIDDM) where both insulin deficiency and insulin resistance may act as underlying pathogenetic mechanisms; which of them predominates may largely determine the optimum treatment. Recently, measure ment of serum C-peptide has been demon strated to allow for increased confidence in Kyllâslincn assessing the degree of dependence on insu lin treatment in diabetics [4,7,11,12,15,21,23]. Proinsulin is converted to insulin and C-peptide in pancreatic (3-cells and sub sequently these are secreted in equimolar concentrations.…”
mentioning
confidence: 99%
“…)• The median potentiation of plasma C-peptide concentration 6 min post glucagon was 120-140% at the two levels of hyperglycemia. This finding is of clinical interest since plasma C-peptide concen¬ tration 6 min post glucagon has been used in the discrimination between diabetes types (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 89%